Effectiveness of ISSR markers for detecting genomic variability in Panicum miliaceum L. accessions - D. Kh. Arkhestova; A. A. Yakhutlova; A. D. Khaudov; L. Kh. Sokurova; T. V. Kulemina (Труды по прикладной ботанике, генетике и селекции)
Background. Millet is one of the main cereal crops with a wide area of cultivation. Over the past decade, there has been a significant increase in the consumption of millet and its processed products. As a result, the breeding of cultivars with high consumer properties is becoming relevant, requiring knowledge of the genetic diversity of germplasm accessions to identify donors of valuable agronomic traits and select parental forms using ISSR markers.Materials and methods. The analysis with 8 ISSR primers included 21 accessions of Panicum miliaceum L. of various origin from the VIR collection. The DNA of each accession was isolated by the CTAB method, and ISSR analysis was performed in a BioRad T100 Thermal Cycler. Statistical processing was made in the DARwin program (version 6.0.21).Results and conclusion. Eight primers were used to amplify 116 fragments, 62 (53.4%) of which turned out to be polymorphic. To assess the effectiveness of the analyzed primers and identify the polymorphism of millet, basic indicators of their informativeness were calculated and assessed by quantifying four marker parameters. Average PIC (0.27–0.36), EMR (1.38–14.5) and MI (0.12–4.87) values were obtained for most ISSR primers. Four ISSR primers had high Rp values (3.52–6.76) and were the most informative for genotyping. The selected ISSR markers were used to assess the genetic variability of the accessions and identify them. The values of genetic distances (GD) were 0.05–0.21. It was shown that four ISSR markers with the best informativeness values provided sufficient polymorphism to assess the genetic diversity of the analyzed P. miliaceum genotypes and could be recommended for identification of the variability in the genome of millet accessions.